Sistem Pendukung Keputusan Penilaian Kinerja Mekanik Menggunakan Metode AHP dan TOPSIS - Noprida Arianto; Nurahman Nurahman (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Decision Support (DSS) is a system that was built to solve problems that are managerial or corporate organization designed to develop the effectiveness and productivity of managers to solve problems. PT. Auto Mobil Prima is one of the most popular Hino dealers in Sampit. This dealer is located in Central Kalimantan, precisely on Jl. General Sudirman Km. 2 Sampit and has branches in Pangkalan Bun and Palangka Raya. This study aims to assess the performance of the mechanical employees at PT. Prime Cars. In the assessment process, it is difficult for management to give weight to each criterion. So that it takes quite a long time, there is no system for decision makers that supports the performance appraisal of employees in the mechanics department. From the problems above and based on previous research, it is necessary to have a decision support system for evaluating the performance of employees in the mechanics department at PT. Auto Mobil Prima, one of the methods that can be used is AHP (Anailitycal Hierarchy Process) and TOPSIS (Technique For Others Reference by Similarity to Ideal Solution). This method was chosen because it is able to complete employee performance appraisals based on predetermined criteria. The results of this study are a website for a mechanical performance appraisal decision support system using the AHP (Anailitycal Hierarchy Process) and TOPSIS (Technique For Others Reference by Similarity to Ideal Solution) methods. So it is hoped that it can help PT. Auto Mobil Prima is a more objective mechanical performance decision maker